1990
DOI: 10.1098/rspb.1990.0092
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells cultured from human umbilical vein release ATP, substance P and acetylcholine in response to increased flow

Abstract: Cultured human umbilical vein endothelial cells superfused with Krebs' solution were used to investigate release of ATP, substance P and acetycholine with shear stress. ATP was consistently released when the cells were exposed to increased flow rate; release was rapid, had declined by 1 min and occurred upon a second exposure. Release of substance P and acetylcholine was more varied; increased shear stress led to release of substance P from 4 out of 16 endothelial-cell columns, whereas acetylcholine was releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(33 citation statements)
references
References 14 publications
3
30
0
Order By: Relevance
“…It has been shown that P2 activation leads to increases in concentration of intracellular calcium and PGE2 release (Naemsch et al, 2001). ATP, which activates this pathway, is typically released by bone, endothelial and epithelial cells and fibroblasts under stress conditions, acting as a DAMP/alarmin (Bodin & Burnstock, 1998;Burnstock, 1999;Furuya, Sokabe & Furuya, 2005;Grygorczyk & Hanrahan, 1997;John & Barakat, 2001;Katsuragi & Migita, 2004;Katz, Boland & Santillan, 2006;Kerkweg & de Groot, 2005;Milner et al, 1992;Milner et al, 1990b;Ohata et al, 1997;Patel et al, 2005;Romanello et al, 2001;Sauer, Hescheler & Wartenberg, 2000;Yamamoto et al, 2003).…”
Section: P2x7 Receptor: a Possible Mediator Of Orthodontic Mechanotramentioning
confidence: 99%
“…It has been shown that P2 activation leads to increases in concentration of intracellular calcium and PGE2 release (Naemsch et al, 2001). ATP, which activates this pathway, is typically released by bone, endothelial and epithelial cells and fibroblasts under stress conditions, acting as a DAMP/alarmin (Bodin & Burnstock, 1998;Burnstock, 1999;Furuya, Sokabe & Furuya, 2005;Grygorczyk & Hanrahan, 1997;John & Barakat, 2001;Katsuragi & Migita, 2004;Katz, Boland & Santillan, 2006;Kerkweg & de Groot, 2005;Milner et al, 1992;Milner et al, 1990b;Ohata et al, 1997;Patel et al, 2005;Romanello et al, 2001;Sauer, Hescheler & Wartenberg, 2000;Yamamoto et al, 2003).…”
Section: P2x7 Receptor: a Possible Mediator Of Orthodontic Mechanotramentioning
confidence: 99%
“…It is known that fluid flow stimulates production of ATP by cultured EC (Milner et al, 1990) and the release rate is thought to increase with the applied wall shear stress (Yamamoto et al, 2003). Following John and Barakat (2001), we consider two possible production rate functions, both of which are increasing functions of wall shear stress, r w ( x): (11) where So, Tm ~ 0 are constants.…”
Section: Model For Atpmentioning
confidence: 99%
“…They also contain heterogeneous cytoplasmic stores of agonists that stimulate EDRF synthesis, including bradykinin, vasopressin, angiotensin II, 5-HT and substance P, although it is unclear whether these are taken up or synthesized de novo (Bodin, Bailey & Burnstock, 1991;Loesch, Bodin & Burnstock, 1991;Ralevic, Lincoln & Burnstock, 1992). Increases in flow stimulate release of ATP, and less consistently acetylcholine and substance P, from isolated endothelial cells, and substance P, vasopressin and ATP can be detected in the effluent from perfused rat hindlimb and rabbit brain preparations on increasing flow (Milner, Kirkpatrick, Ralevic, Toothill, Pearson & Burnstock, 1990;Ralevic, Milner, Hudlicka', Kristek & Burnstock, 1990;Domer, Alexander, Milner, Bodin & Burnstock, 1992). That ATP may be released in functionally active concentrations has been demonstrated in rat lung in which the consequences of flow-related ATP release are blocked by suramin, a P2 purinoreceptor antagonist, resulting in elevation of perfusion pressure (Hassessian, Bodin & Burnstock, 1993).…”
Section: Flow-induced Release Of Endothelium-dependent Agonistsmentioning
confidence: 99%